Notch sensitivity of mammalian mineralized tissues in impact - Currey, John D.; Brear, Kevin; Zioupos, Peter (The Royal Society, 2004)
The toughness of bone is an important feature in preventing it from fracturing. We consider the notch sensitivity in impact, and the associations between brittleness, notch sensitivity and post–yield energy absorption of mammalian mineralized tissues. Specimens of bone–like tissues covering a wide range of mineralization were broken, either notched or un–notched, in impact. The greater the mineral content, the greater was the notch sensitivity. Also, the more brittle tissues dissipated the least post–yield energy and were the most notch sensitive. It is suggested that since antler bone, the least mineralized of all known mammalian mineralized tissues, seems to be notch insensitive in impact, no adaptive purpose would be served by having mineralized tissues of a lower mineralization than antler. This may explain the lower cut–off in mineralization seen in mammals
Keywords: Mineral content; Notch sensitivity; Energy absorption; Impact strength; Bone